Gambaran Karakteristik yang Mempengaruhi Tingkat Depresi Lansia di UPTD PSLU Blitar - Erni Setiyorini (STIKes Patria Husada Blitar, 2016)
The indicators of health of a nation is the increasing life expectancy, as shown by an increase in the proportion of the elderly population. The prevalence of elderly with depression has increased and characteristic factors are among the factors triggering the onset of depression in the elderly. The purpose of this research was to determine the characteristics of the elderly in UPTD PSLU Blitar, determine the level of elderly depression and to identify the characteristics of the elderly which affects the rate of depression in the elderly in UPTD PSLU Blitar. The design of this research was descriptive. The population in this study was elderly who live in UPT PSLU much as 52 people. The sample was 28 people taken by purposive sampling. The research instrument used GDS (Geriatric Depression Scale). The results of the research could be concluded that elderly in UPT PSLU Blitar depressed in probability depressed category 42.7% and average depressed category was 14.2%. Based on the age, the highest proportion of probability depression in the elderly aged 60-74 years 21.42%, according to the gender distribution of the largest depression in women is 35.71% probability depression, based on marital status as much as 14.28% of elderly depressed being, based level of education, elderly people who are not in school most experienced probability depression that is 28.57%. For further research this study could be a baseline for future studies, for UPT PSLU the research data could be used as an input to provide appropriate interventions for depression in the elderly.